The Impact of Using Technology as Media of Studying toward English Students's Speaking Ability During Covid -19 - elmiwati; Mutiara Yulia Effendi (Miftahul Ulum, 2023)
The Coronavirus disease 2019 (COVID- 19) pandemic has brought tremendous impact on all aspects of life. One of the biggest impacts in the world that causing educational disruptions worldwide. without the exception of Indonesia, which requires learning to be held online by using various learning delivery medias. The purpose of the research were to find out how frequently students use technology in learning English, what technologies did students use in improving their speaking ability, to know whether the students enjoyed using technology or not and to find out the impact of technology used on English speaking ability. This research presented data showing the positive effects of digital technology in enabling students to be more proficient in learning English. The results showed that learning English as a foreign language through the use of computer software, social networking sites, online video and audio tools (i.e., YouTube, Skype, and MP3), and smartphone and tablet applications were shown to increase students' learning of English.